Perspectives on China's rise in Namibia: the effects on foreign policy and domestic politics - Amadhila, Nelago Ndapandula Ndanyanyukwa (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2012)
This thesis analyses the different levels at which China's presence in Namibia affects Namibia's domestic politics and foreign policy from a constructivist viewpoint. Constructivist theory is used to examine the different perceptions of the Chinese in Namibia and how these inform Namibian politics and Sino-Namibian relations. These perceptions are formed at different levels of society in formal and informal relations, state-to-state, state-to-business,business-to-business and individual-to-group relations. The way in which perceptions of Chinese involvement in Namibia at the grassroots level of society differ from those at the top increasingly has an effect on domestic Namibian politics and, as such, Sino-Namibian relations. This identifies official and non-official perceptions of China's political, economic and social presence to determine the effects of grassroots on China vis-Ã -vis official perceptions in Namibian politics and the effects of grassroots views on Namibian politics and on official views and state behaviour towards China and China's presence in the country.
Keywords: Namibia -- Relations -- China|China -- Relations -- Namibia|Namibia -- Politics and government -- Chinese influences|Namibia -- Economic conditions -- Chinese influences